2019
DOI: 10.1021/jacs.9b12564
|View full text |Cite
|
Sign up to set email alerts
|

Making the Right Link to Theranostics: The Photophysical and Biological Properties of Dinuclear RuII–ReI dppz Complexes Depend on Their Tether

Abstract: The synthesis of a new dinuclear complexes containing linked Ru II (dppz) and Re I (dppz) moieties is reported. The photophysical and biological properties of the new complex, which incorporates a N,N'-bis(4-pyridylmethyl)-1,6-hexanediamine tether ligand, are compared to a previously reported Ru II /Re I complex linked by a simple dipyridyl alkane ligand. Although both complexes bind to DNA with similar affinities, steady state and time resolved photophysical studies reveal that the nature of the linker affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 75 publications
0
45
0
Order By: Relevance
“…Recently, the same research group also developed novel Re I Ru II complexes linked by simple dipyridyl alkane ligands. [40] This time the typical tris-bisimine Ru II structure was substituted for a tripodal tris(pyrazol-1-yl)methane (tpm), a dipyrido[3,2a:2',3'-c]phenazine (dppz) and a dipyridyl alkane ligand that was used as connector between the Ru II and Re I fragments (Figure 14). The nature of the dipyridyl linkers affects the biodistribution as well as photostability.…”
Section: Unconventional Heterometallic-based Bioprobesmentioning
confidence: 99%
“…Recently, the same research group also developed novel Re I Ru II complexes linked by simple dipyridyl alkane ligands. [40] This time the typical tris-bisimine Ru II structure was substituted for a tripodal tris(pyrazol-1-yl)methane (tpm), a dipyrido[3,2a:2',3'-c]phenazine (dppz) and a dipyridyl alkane ligand that was used as connector between the Ru II and Re I fragments (Figure 14). The nature of the dipyridyl linkers affects the biodistribution as well as photostability.…”
Section: Unconventional Heterometallic-based Bioprobesmentioning
confidence: 99%
“…Conditions have been previously described 9,39 ; briefly, soluble cytosolic GFP for point spread function (PSF) calculation and Di4A were excited with at 488 nm; emission was detected between 500 and 550 nm for GFP and for Di4A two channels were recorded, 500-580 nm and 620 to 750nm. The STED depletion laser beam was a pulsed 775 nm; the emission was collected from 620 to 710 nm with a gating between 2 and 6.5 ns as in previous works 55,56 , and the pinhole was set to one Airy unit at 580nm. For a cleaner emission the excitation lines had a clean-up notch filter (NF) in the optical pathway.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] In the past few years, our group and others demonstrated that phosphorescent metal complexes can not only kill cancer cells effectively, but also provide valuable information on their action mechanisms by monitoring the cellular localization, 14 dynamic imaging/tracking of the subcellular organelles, 15 and even quantitatively measuring the parameters of the surrounding microenvironment. 16 Combined with super-resolution imaging, 17,18 two/multi-photon imaging 12 and phosphorescence lifetime imaging (PLIM) 16 technologies, more accurate and detailed information can be obtained. More importantly, these compounds have the potential to be developed as research tools for life science to accurately monitor the behaviour of subcellular organelles, functions of biomacromolecules, and changes in micro-environmental parameters (e.g., hypoxia, pH, viscosity and polarity) during various biological processes.…”
Section: Introductionmentioning
confidence: 99%